Alteration of the gut microbiota and metabolite phenylacetylglutamine in patients with severe chronic heart failure - Zhang, Zhendong; Cai, Bin; Sun, Yanzhuan; Deng, Haiyan; Wang, Hongwei; Qiao, Zengyong (Frontiers in Cardiovascular Medicine, 2023)
Chronic Heart Failure (CHF) is the end result of nearly all cardiovascular disease and is the leading cause of deaths worldwide. Studies have demonstrated that intestinal flora has a close relationship with the development of Cardiovascular Disease (CVD) and plays a vital role in the disease evolution process. Phenylacetylglutamine (PAGln) a metabolite of the intestinal flora, is one of the common chronic kidney disease toxins. Its concentrations in plasma were higher in patients with major adverse cardiovascular events (MACE) however, its variation in patients with various degrees of CHF has rarely been reported. Therefore, we collected stool and plasma samples from 22 healthy controls, 29 patients with NYHA Class III and 29 patients with NYHA Class IV CHF (NYHA stands for New York Heart Association) from the Department of Cardiology of Shanghai Fengxian District Central Hospital. Next, we analyzed these samples by performing bacterial 16S ribosomal RNA gene sequencing and liquid chromatography tandem mass spectrometry. The result shows: The Chao 1 index was significantly lower in both NYHA class III and NYHA class IV than it was in the control group. The beta diversity was substantially dissimilar across the three groups. The linear discriminant analysis effect size analysis (LEfSe) showed that the bacterial species with the largest differences were Lachnospiraceae in control group, Enterobacteriaceae in NYHA class III, and Escherichia in NYHA class IV. The concentration of PAGln was significantly different between CHF and control groups and increased with the severity of heart failure. Finally, the correlation analysis represented that Parabacteroides and Bacteroides were negatively correlated to brain natriuretic peptide (BNP) and PAGln; Romboutsia and Blautia adversely associated with PAGln; Klebsiella was positively interrelated with BNP; Escherichia-Shigella was positively correlated with PAGln and BNP; Alistipes was contrasted with BNP; and Parabacteroides was negatively correlated with the left ventricular end-diastolic diameter (LVEDD). This study presented that the intestinal flora and its metabolite PAGln were altered with different grades of CHF and illustrated the effects of the gut flora and its metabolite on CHF.